Safety in Numbers or Lost in the Crowd? Litigation of Mass Claims and Access to Justice in Ontario - Chiodo, Suzanne (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
Ontario’s Class Proceedings Act [CPA] is 30 years old. In the past three decades, it has inspired similar legislation across Canada and around the world, and its capacity for bringing about social change has been widely acknowledged. But, like all things that mature, some cracks are beginning to show. The certification test under section 5 of the CPA has been made more restrictive by recent legislative amendments. In addition, class action practitioners are starting to recognize that the CPA can be a blunt instrument and that some mass claims are better litigated outside of that context. While smaller claims may find safety in numbers in a class action, larger claims that require more individualized treatment may get lost in the crowd. Outside of the CPA, however, there is minimal guidance in this area, and this can lead to uncertainty and delay.This article proposes a set of informal guidelines for the litigation of mass claims in Ontario, informed by multidistrict litigation in the US and group litigation in England & Wales, as well as the theory and history of mass claims typology. This guidance will reduce uncertainty and delay by facilitating agreement between parties on procedural steps and provide much-needed direction for a growing phenomenon.